A New Heat-Warning-System Based on a Wireless Body Area Network for Protecting Firefighters in Indoor Operations - Dietz, Marco; Striegel, Martin; Weigel, Robert; Hagelauer, Amelie Marietta (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2018)
A new Heat-Warning-System is presented to protect firefighters in indoor operations. With the proposed Heat-Warning-System, a permanent monitoring of the body core temperature can be done, in order to protect the firefighter from a collapse. Furthermore, by placing several temperature sensors around the thorax on particular positions, the relative location of dangerous heat sources can be estimated. For the placement of the sensor nodes, an empirical channel model in combination with a cuboid body model was used, to estimate the individual transmission path losses by taking into account the influence of the human body. Finally, the Heat-Warning-System is tested and moreover the locating functionality of dangerous heat sources is shown.